2003
DOI: 10.1021/ja0353053
|View full text |Cite
|
Sign up to set email alerts
|

On the Electronic Origins of Structural Isomerism in the Iron−Sulfur Cubane, [(C5H5)4Fe4S4]2+

Abstract: Density functional theory provides new insights into the structural isomerism observed in the cyclopentadienyl-capped iron-sulfur cluster, [(C(5)H(5))(4)Fe(4)S(4)](2+). Two distinct, closely spaced minima have been located, a triplet with D(2) symmetry and a C(2)-symmetric singlet, both of which correspond closely to the structure of one of the known crystal forms of the cation. Thus, the structural diversity in these species reflects genuine molecular bistability rather than simple solid-state packing effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Both procedures correctly predict two Fe-l 3 -S bonds to be substantially longer than the third Fe-l 3 -S bond, in agreement with experiment, showing that in both experiment and theory, the cluster is not fully valence delocalized over equivalent centers, but rather consists of three isomers, with two of the irons equivalent and valence delocalized, as was first realized from Mö ssbauer spectroscopy [1]. Interestingly, a DFT study recently found two different isomers of a [Fe 4 S 4 ] cluster consistent with two different crystal forms [64]. Finally, the computed through-space Fe-Fe distances were 2.61 Å , 2.66 Å , and 2.68 Å , giving an average of 2.65 Å , compared to 2.70 Å from experiment.…”
Section: The Fe 3 S 4 Clusters: Structuresupporting
confidence: 85%
“…Both procedures correctly predict two Fe-l 3 -S bonds to be substantially longer than the third Fe-l 3 -S bond, in agreement with experiment, showing that in both experiment and theory, the cluster is not fully valence delocalized over equivalent centers, but rather consists of three isomers, with two of the irons equivalent and valence delocalized, as was first realized from Mö ssbauer spectroscopy [1]. Interestingly, a DFT study recently found two different isomers of a [Fe 4 S 4 ] cluster consistent with two different crystal forms [64]. Finally, the computed through-space Fe-Fe distances were 2.61 Å , 2.66 Å , and 2.68 Å , giving an average of 2.65 Å , compared to 2.70 Å from experiment.…”
Section: The Fe 3 S 4 Clusters: Structuresupporting
confidence: 85%
“…In the case of M ~Ru the more diffuse 4d orbitals stabilise the C 2 singlet form, with the D 2 state providing a low-energy pathway allowing dynamic exchange of the Ru-Ru bonds. 32 A computational study of the reaction of [Ru 3 H 5 Cp* 3 ] (35) with cyclopentadiene leading to a trinuclear 2-methylruthenacyclopentadiene suggests a cooperative role of the three metal centres. 33 35,36 Reduction (LiAlH 4 ) of [RuCl(tmeda)Cp] afforded the cyclopentadienyl-capped trigonal bipyramidal cluster [Ru 5 H 7 Cp 5 ] (36), which is fluxional in solution exchanging axial and equatorial vertexes, via a Berry pseudorotation-like process.…”
Section: Methodsmentioning
confidence: 99%
“…The cubane‐like core is the universal motif of all photosynthetic enzymes responsible for photocatalytic water splitting in the oxygen evolving complexes in green plants [10] . In fact, many theoretical investigations have been conducted to understand the mechanism behind diverse roles played by these ubiquitous clusters [11–13] . Enzymes that resemble the iron‐sulfur clusters, Fe 4 S 4 , present in the active sites of photosystems have been extensively used in biomimetic inorganic chemistry [14] .…”
Section: Introductionmentioning
confidence: 99%
“… [10] In fact, many theoretical investigations have been conducted to understand the mechanism behind diverse roles played by these ubiquitous clusters. [ 11 , 12 , 13 ] Enzymes that resemble the iron‐sulfur clusters, Fe 4 S 4 , present in the active sites of photosystems have been extensively used in biomimetic inorganic chemistry. [14] The Fe 4 S 4 cubane clusters have been also exploited in the catalytic chalcogel frameworks for the commercial production of hydrogen .…”
Section: Introductionmentioning
confidence: 99%